Taal als een strategisch spel - Sevcikova Lepkova, Katerina (Acta Neerlandica, 2024)
This article describes and analyses communication as a complex action embedded in a social and cultural context. The communicative action consists of explicit language utterance and of implicit presuppositions of the speaker who is entering the communicative act with a specific communicative goal. This goal can be reached only if the implicit presuppositions of the speaker are mutually shared among the participants of the discussion. The social and cultural context can be seen as implicit presuppositions of the speaker and these contextual presuppositions are playing an important role in the communicative situations. Habermas divides the communicative acts according to the level of rationality and according to the communicative goal of the speaker into different types. The rational discourses can be analyzed by mean of argumentative analysis which can be also used for a reconstruction of communicative acts which happened in the past.